Identification of The Tourism Potential of Firdaus Park Sriwijaya University - Azizah Husin; Randi Pranando; Dian Sri Andriani (Publikasi Indonesia, 2022)
This study aims to identify the tourism potential of Taman Firdaus of Sriwijaya University according to component 4A and SWOT analysis. This type of research is descriptive with a qualitative approach. Data was collected through interviews, observation, and documentation. The research subjects were students of Sriwijaya University and the manager of the construction of Taman Firdaus. The results obtained in this study are 1) Identification of the potential of Taman Firdaus through the condition of the 4A components, namely Attraction, Amenity, Accessibility, and Ancilliary. The attractions in Taman Firdaus are artificial lakes and fruit plantations. Meanwhile, in Amenity, tourist facilities have not been built, but there is already a road to Taman Firdaus as an accessibility component, although it has not been asphalted yet. As for additional services for the Ancilliary component, there is already a security team in charge of guarding the Taman Firdaus. 2) SWOT analysis shows that the tourism potential in Taman Firdaus is a strategic location and a large area of ??land. However, there are weaknesses in access to the location which is still in the form of soil and gravel and does not yet have supporting tourism facilities and infrastructure. In addition, there is an opportunity to make Taman Firdaus an object of ecotourism education so that it can create jobs for the community and students. Meanwhile, the threat encountered at the location is the large number of wild animals that can endanger the safety of visitors.